Pengembangan Media Pembelajaran Interaktif pada Materi Relasi dan Fungsi - Susanty Pakaya; Evi Hulukati (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
This research is development research aimed at producing valid and practical products in the form of interactive learning media. The research employed a development research methode using a four-D (Define, Design, Develop and Disseminate) development model. It was conducted on students of class VIII at SMP N 1 Kwandang, North Gorontalo Regency, during the odd semester of the 2022 / 2023 academic year. The results indicated that the quality of the product being developed met the criteria of validity, practicality, and effectiveness. This was shown from the validation results for both media and material with an average validator score of 4.67, falling within the highly valid category. The analysis of the practicality aspect in the small group trials scored with 84.17% meeting the very practical criteria and the large group trials achieved an average score of 84.88%, also meeting the very practical criteria. Based on these findings, it can be concluded that the interactive learning media assisted by the kinemaster application that was developed is valid and practical for the topic of Relations and Functions for class VIII at SMP N 1 Kwandang.